The Indirect Antithesis in the "Intesab" Poem by Farouq Shusha (Journal of Hama University, 2024)
Indirect Antithesis is an essential structure in Farouq Shusha's poetry, as its significance and effectiveness cannot be limited to the sentence or line level. Rather, it extends to include passages of the modernist poem as a whole, and from here the research takes its legitimacy in supplementing the previous studies with another aspect that it did not illuminate, and revealing the indications that the antithesis serves the modernist poem, as well as its impactful effectiveness that depends on the originator, and its influencing importance in the recipient. The researcher uses the descriptive analytical approach while benefiting from the mechanisms of the stylistic approach in analyzing the poem "Intesab" to achieve the objectives of the research and answer its questions.The research was built on an introduction that included the concept of Antithesis, and included the objectives of the research, its methodology, its importance, its problem, the reasons for its study and its sample, as well as previous studies.She presented the research with according to a variety outline such as: Antithesis was a stylistic phenomenon that characterized this poetry. It's significance expanded in the poem, and the Originator employed it to achieve a Rhetorical objectives in the poem full of passion, then she ended the research with an index of sources and references.
Keywords: Antithesis- Indirect- Originator – Recipient